2022
DOI: 10.23938/assn.0984
|View full text |Cite
|
Sign up to set email alerts
|

Presence and influence of attention deficit hyperactivity disorder symptoms in adults with an eating disorder

Abstract: Resumen Fundamento: La coexistencia de trastornos de la conducta alimentaria (TCA) y del trastorno por déficit de atención e hiperactividad (TDAH) es frecuente. El objetivo del estudio fue cuantificar la presencia de sintomatología TDAH en pacientes adultos con TCA y evaluar posibles correlaciones entre ambas sintomatologías. Material y métodos: Estudio transversal en pacientes con TCA. Se cumplimentaron los cuestionarios Eating Attitudes Test de 40 ítems (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This may be the case in treatment of ADHD with stimulants, which can occasionally induce mood swings, mania and bipolar disorder 4 . That could explain some cases of extreme decreased appetite (and weight) in children with ADHD treated with stimulants that can resemble anorexia nervosa , but that does not seem to be the case in the paper we are commenting on 1 . Symptom overlap may generate the diagnosis of both disorders (probably not the case in ED and ADHD).…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…This may be the case in treatment of ADHD with stimulants, which can occasionally induce mood swings, mania and bipolar disorder 4 . That could explain some cases of extreme decreased appetite (and weight) in children with ADHD treated with stimulants that can resemble anorexia nervosa , but that does not seem to be the case in the paper we are commenting on 1 . Symptom overlap may generate the diagnosis of both disorders (probably not the case in ED and ADHD).…”
mentioning
confidence: 82%
“…A recent cross-sectional study carried out at an outpatient Eating Disorders program in San Sebastian (Guipúzcoa, Spain), consisting of 108 adult patients diagnosed with Eating Disorders (ED), found a disproportionately elevated rate of Attention Deficit Hyperactivity disorder (ADHD) diagnosis when using the Adult ADHD Self-Report Scale (ASRS-v1.1) 1 . Ruiz Feliu from the Donostia-Amara Mental Health Center, in collaboration with colleagues from the University of Navarra Clinic, Hospital Universitario Donostia and Ansoain Mental Health Center, discovered high ASRS scores in 42.6% of the patients 1 , which is a rate about 17 times higher than the expected rate of ADHD diagnosis in the general adult population (2.5%) 2 . They also observed a higher correlation of ADHD and ED in binge-purge types of eating disorder, those most commonly associated with greater impulsivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, these harmful yet often unfounded claims contribute to an underestimated risk factor in the lives of individuals with ADHD (Kaushik et al, 2016). A consensus belief found across the literature states that stigmatization directly causes harm to patients of ADHD by increasing resistance to seeking proper medical treatment (Rummans et al, 2022;Vaingankar et al, 2017), heightened psychological distress (Masuch et al, 2019;Hinshaw & Stier, 2007), eating disorders (Feliu et al, 2022), substance abuse (Rohner et al, 2023), as well as an increased risk for other adverse psychiatric disorders due to its comorbidity (Perumareddi & Majarwitz, 2023). Additionally, studies have demonstrated a correlation between experienced stigmatization and worsened treatment adherence, treatment e cacy, symptom aggravation, life satisfaction, and mental well-being (Mueller et al, 2012), culminating in a significantly lower quality of life for those a ected by ADHD.…”
Section: Literature Reviewmentioning
confidence: 99%